ANALISIS PENERAPAN INTERNAL CONTROL TRANSAKSI PENGELUARAN KAS PADA PT SUVARNA BHUMI INDONESIA - Arifiani, Fitria Retno; Utami, Helianti; Islam, Ajeng Aina Nur (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The development of the property and real estate sector is said to be one of the most attractive sectors in Indonesia. Property and real estate is one of the sub-sectors of service companies which is currently booming and growing rapidly. In operational activities, cash disbursement activities are an important component in an entity. Thus, it is necessary to apply internal controls to protect company assets from fraud. This study aims to analyze the effectiveness of internal control implementation in accordance with the 2013 COSO Internal Control framework on cash disbursement activities at PT Suvarna Bhumi Indonesia. The data used in this research is primary data taken by observing, interviewing, and documenting. This research was conducted at the financial division of PT Suvarna Bhumi Indonesia which is located at Jl. Drs. Moh. Hatta No. 181, Pendem, Junrejo, Batu City. Based on the research results, the level of effectiveness of internal control implementation as indicated by the implementation of the basic components of COSO 2013, namely control environment, risk assessment, control activities, information and communication, and monitoring activities can be said to be very effective. However, there are several basic components of COSO 2013 that have not been fully implemented in accordance with existing theory, such as workload reviews that have not been implemented, management is not involved in the decision-making process, and internal communication has not been effective.